An assessment on genus Laristania Amsel, 1951 (Lepidoptera: Pyralidae: Phycitinae) and a new species from Turkey - Akin, Kesran; Seven, Erdem (Zootaxa, 2021)
Laristania beyarslani sp. nov., a new species of Phycitinae (Pyralidae) from Turkey, is described herein, and compared with other known species of the genus Laristania Amsel, 1951. The distribution area of all Laristania species and assessment on the morphology of some species are presented. Habitus, male and female genitalia of the new species are illustrated. The male genitalia of all species in the genus are compared. Besides, photos of adult, male and female genitalia of L. taftanella (Amsel, 1954), and adult and male genitalia of L. aspergella (Ragonot, 1887) are provided.